Comeback as workers’ party with left-authoritarian communitarianism? Contexts, ideologemes and fallacies of an emerging rightist social-democratic party project using the example of the British Labour Party - Puller, Armin (Momentum Quarterly, 2022)
Many social-democratic parties are currently characterised by a polarisation of the political strategies of a social-liberal value orientation and a left-authoritarian communitarianism. The article analyses the second strategy by using the example of the British Labour Party, where this strategy has formed a tendency that has gained some influence between 2010 and 2015 as well as since the change of leadership under Keir Starmer. It rests upon a rejection of economic and cultural liberalism and aims to win back working-class milieus by advocating social conservatism and challenging migration. After presenting the contexts of this strategy within Labour, the second part draws on the discourse of left-authoritarian communitarianism and its political positions, ideological references as well as attempts to construct a new narrative of Labour’s history and the labour movement. The third part highlights analytical fallacies and dangers of this strategy resulting in a retrotopian and conservative conceptualisation of the common good producing the effects of obstructing an alliance of the left and unity of the working class as well as depoliticising social injustices by displacing them as issues of culture.